Arbitrage Asset Pricing Under Exchange Risk. - Ikeda, Shinsuke (Journal of Finance, 1991)
This paper extends the arbitrage pricing theory to an international setting. Specifying a linear factor return-generating model in local currency terms, the author shows that the usual risk-diversification rule in the arbitrage pricing theory does not yield a riskless portfolio unless currency fluctuations obey the same factor model as asset returns. The author then considers an arbitrage portfolio whose exchange risk is hedged by foreign riskless bonds. Under the resulting no-arbitrage conditions, the expected returns are not on the same hyperplane, unlike the closed-economy arbitrage pricing theory, unless they are adjusted by the cost of exchange risk hedging.